Fault signal propagation through the PMSM motor drive systems - Li, Jing; Sumner, M.; Arellano-Padilla, J.; Zhang, He (IEEE, 2017)
This paper describes how a mechanical disturbance on the shaft of a variable speed permanent magnet motor (PMSM) is propagated to the supply input side of the drive system, and therefore may be detected by monitoring specific frequency components in the rectifier input current. The propagation of the disturbance from the torque disturbance, to the motor current, then to the dc link current and finally to the rectifier input current is derived as a series of transfer functions so that both the frequency and the amplitude of the disturbance component in the rectifier input current can be predicted for a specific mechanical disturbance. The limitations to detect the mechanical fault by monitoring only the supply currents are also addressed. Simulation and experimental results are presented to demonstrate the accuracy of the quantitative analysis, and the potential for fault detection using the rectifier input currents.